Effectiveness of brodalumab in improving itching and skin pain in Japanese patients with psoriasis: The ProLOGUE study. Issue 4 (20th December 2022) - Honma, Masaru; Kanai, Yasumasa; Murotani, Kenta; Ito, Kei; Ohata, Chika; Yamazaki, Fumikazu; Saeki, Hidehisa; Seishima, Mariko; Mizutani, Yoko; Kitabayashi, Hiroki; Imafuku, Shinichi
Abstract: Itching and skin pain are bothersome symptoms of psoriasis, but evidence is limited regarding the treatment effectiveness on these symptoms in daily clinical settings. We assessed the changes in the levels of itching and skin pain after brodalumab treatment in Japanese patients with psoriasis using patient‐reported outcomes (PROs). Patients with psoriasis who have inadequate response to existing treatments were enrolled in the single‐arm, open‐label, multicenter, prospective ProLOGUE study and received brodalumab 210 mg subcutaneously in daily clinical practice. Psoriasis Area and Severity Index (PASI) and PRO assessments were performed at baseline and weeks 12 and 48. Seventy‐three patients (men, 82.2%; median age, 54.0 years) were enrolled. The Itch Numeric Rating Scale (NRS; p  < 0.0001 at weeks 12 and 48) and Skin Pain NRS (week 12, p  = 0.0004; week 48, p  < 0.0001) scores significantly decreased from baseline. The Itch NRS score was significantly higher in patients with a Dermatology Life Quality Index (DLQI) score of ≥2 (vs. 0/1; p  < 0.0001 at weeks 12 and 48) and in patients with a Treatment Satisfaction Questionnaire for Medication‐9 (TSQM‐9) global satisfaction domain score of ≤70% (vs. >70%; week 12, p  = 0.0120; week 48, p  = 0.0348). The Itch NRS score cutoff value for achieving a PASI score of ≤2, DLQI score of 0/1, and TSQM‐9 global satisfaction domain score of >70% was 1 at week 12 and 0 at week 48. Brodalumab treatment was associated with improvement in itching and skin pain in Japanese patients with psoriasis. An Itch NRS score of 0 can be a long‐term treatment goal for psoriasis (Japan Registry of Clinical Trials identifier: jRCTs031180037).